An analytical framework for the modelling and evaluation of the mobile agent based distributed network management paradigm. (29th December 2008) - Ye, Jian; Papavassiliou, Symeon
The new emerging technology of Mobile Agents (MAs) has arisen in the distributed programming field as a potential flexible way of managing resources of a distributed system. In this paper a generic framework that can be used for the evaluation and analysis of the performance and tradeoffs of the MA management paradigm is introduced. One key principle of the proposed framework, is that it provides a common paradigm that can accommodate both one-time and periodic management tasks. We illustrate how the developed analytical framework can be used to quantitatively evaluate the performances and tradeoffs in different computing paradigms, by comparing the performances of the MA based paradigm with the corresponding ones of the Client-Server (CS) mode under different scenarios. We also discuss how different MA dissemination strategies could affect the performances of the mobile agent based network management approach.